2022
DOI: 10.1039/d1en00740h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of growth-promotion and Se-enrichment inBrassica chinensisL. by selenium nanomaterials: beneficial rhizosphere microorganisms, nutrient availability, and photosynthesis

Abstract: Maintaining a proper content of selenium (Se) in food is particularly important for human health. However, the mechanisms of uptake and enrichment of Se ENMs in crops are still unclear....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…4 The dissolved organic carbon in the soil extracts likely adsorbed on NPs surface, which resulted in increased electrostatic and steric stability and thus reduced aggregation of particles in soil solutions, thus facilitating continuous dissolution of the particles. 20 Notably, Se NPs may also facilitate microbial growth, 21 which may further increase the possibility of microbial-induced Se oxidation and dissolution in the soil extract. Effects of Se NPs on Lettuce Growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The dissolved organic carbon in the soil extracts likely adsorbed on NPs surface, which resulted in increased electrostatic and steric stability and thus reduced aggregation of particles in soil solutions, thus facilitating continuous dissolution of the particles. 20 Notably, Se NPs may also facilitate microbial growth, 21 which may further increase the possibility of microbial-induced Se oxidation and dissolution in the soil extract. Effects of Se NPs on Lettuce Growth.…”
Section: Resultsmentioning
confidence: 99%
“…A few recent studies have explored the use of NPs to control beneficial rhizosphere microbes and promote plant growth. For example, Wang et al found that Se NPs at 0.5 mg/kg in soil improved the abundance of beneficial rhizosphere Pseudomonas and Bacillus, which contributed to Se uptake and yield increase in Brassica Chinensis L. 21 Similarly, long-term exposure to 50 mg/kg of Ag NPs was reported to alter the structure and composition of the bacterial community in the lettuce rhizosphere, potentially by regulation of bacterial groups associated with nutrient (e.g., N and S) cycling and stress tolerance. 48 Our results suggest that the abundance of bacterial endophytes associated with plant N assimilation (e.g., Azospirillum, Paenibacillus, and Allorhizobium-Neorhizobium-Parahizobium-Rhizobium) was significantly improved by Se NPs in F.o.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Improving nutritional status, enhancing resistance, and regulating gene expression in plants could be achieved by engineered nanomaterials (ENMs). [4][5][6] Besides, nanoscale agrochemicals are typically 20-30% more effective than conventional products in agricultural applications. 7 Tomatoes (Solanum lycopersicum L.) are one of the most widely consumed economic crops, and global tomato production reached 180.8 million tons in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Improving nutritional status, enhancing resistance, and regulating gene expression in plants could be achieved by engineered nanomaterials (ENMs). 4–6 Besides, nanoscale agrochemicals are typically 20–30% more effective than conventional products in agricultural applications. 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation